2012
DOI: 10.4103/0972-5229.99124
|View full text |Cite
|
Sign up to set email alerts
|

An audit of characteristics and outcomes in adult intensive care patients following tracheostomy

Abstract: Background:Tracheostomies are commonly performed on critically ill patients requiring prolonged mechanical ventilation. The purpose of this study was to review our experience with surgical and percutaneous tracheostomies and identify factors affecting outcome.Materials and Methods:Patients who underwent tracheostomy between January 1999 and June 2008 were identified on the basis of Diagnostic Related Group coding and the International Statistical Classification of Diseases and Related Health Problems, Tenth Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…The mean age in this study was 57.4 years as compared with 46.0 to 58.9 years in other studies. 16 Penuelas et al 17 identified a similar trend for a higher rate of reintubation and tracheostomy in those who demonstrated prolonged weaning. The percentage of subjects with a trauma diagnosis reported in these studies ranged from 13.7% to 70%.…”
Section: Discussion Characteristicsmentioning
confidence: 85%
See 2 more Smart Citations
“…The mean age in this study was 57.4 years as compared with 46.0 to 58.9 years in other studies. 16 Penuelas et al 17 identified a similar trend for a higher rate of reintubation and tracheostomy in those who demonstrated prolonged weaning. The percentage of subjects with a trauma diagnosis reported in these studies ranged from 13.7% to 70%.…”
Section: Discussion Characteristicsmentioning
confidence: 85%
“…3,14,16 Nearly half of the subjects in our study had a trauma diagnosis. The mean age in this study was 57.4 years as compared with 46.0 to 58.9 years in other studies.…”
Section: Discussion Characteristicsmentioning
confidence: 92%
See 1 more Smart Citation
“…[ 35 ] Ho et al ., in an audit of characteristics and outcomes in 168 adult ICU patients with tracheostomies concluded that tracheostomy appears to be a relatively safe technique in the ICU population and is not associated with adverse outcomes. [ 36 ] Frutos-Vivar et al . in a vast study in 361 ICUs across 12 countries observed that adjusting by other variables, tracheostomy was independently related with survival in the ICU (OR = 2.22; 95% CI, 1.72-2.86) but in-hospital mortality was similar with or without tracheostomy (39% vs. 40%, P =0.65).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in the literature support our findings. Ho et al, in an audit of characteristics and outcomes in 168 adult ICU patients with tracheostomies concluded that tracheostomy appears to be a relatively safe technique in the ICU population and is not associated with adverse outcomes [21].Frutos-Vivar et al in a vast study in 361 ICUs across 12 countries observed that adjusting by other variables, tracheostomy was independently related with survival in the ICU (OR = 2.22; 95% CI, 1.72-2.86) but in-hospital mortality was similar with or without tracheostomy (39% vs. 40%, P =0.65). [22] The SOFA score (11.77 ± 2.93) were significantly higher in non-survivors in the study (P < 0.05) as shown in [Table 4].…”
Section: Discussion:-mentioning
confidence: 99%